Konsep Epitemologi Paradigma Thomas Khun - Nurkhalis Nurkhalis (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Thomas Kuhn describes that the science truth will be discovered many times  from one object, although the method used changed. Formulation of paradigm theory  sparks that the science truth (legitimated truth) is identical to teleology object, which is  based on detection that is known as final cause. The truth science is not continuous,  improvised, evolutioned, or cumulative. There is paradigm shift actually, which is known  as revolution. Shifting paradigm is equally understood as gestalt switch, which discovers  verification on all at once or not at all. Paradigm shift helps unfolding consciousness that  scientists as unable to discover truth in objectively established manners. Paradigm  designs the worldview’s frame or perspective to be more important, legitimate and  reasonable. This led the detection to revolution or be eliminated due to its experimental  ability in accommodating a new winnowing, which is discovered. Sustained paradigm  will influence normal science as long as anomaly does not exist. The criteria of new  paradigm are neater, more suitable, simpler, and more elegant.